Adaptation of the State Desperation Scale: Its Association with Intolerance of Uncertainty, Entrapment and Resilience - Akyl, Yusuf; Oral, Tuncay; Erdinç, Beste (Anales de Psicología / Annals of Psychology, 2025)
Desperation is a significant conceptual framework that elucidates individuals' profound sense of despair and their impetus to engage in immediate action in response to it. The present investigation comprises three studies aimed at translating the State Desperation Scale into the Turkish language. The 9-item State Desperation Scale was validated using Confirmatory Factor Analysis in Study I, which involved a sample size of 530 participants. The analysis of measurement invariance revealed a lack of structural and metric invariance observed among different gender groups. The analysis of item responses indicated that all items exhibited significant differentiation. The State Desperation Scale demonstrated a high level of reliability, as evidenced by the reliability coefficients of Cronbach's α, McDonald's β, and Guttmann's κ6. In the second study, a sample size of 505 participants was used to conduct both correlation and network analysis. The analysis revealed a significant correlation between desperation and the big five personality traits, as well as depression, anxiety, and stress. Study III employed correlation analysis and structural equation modeling to examine the mediating influence of intolerance of uncertainty and entrapment on the relationship between desperation and psychological resilience. The sample size for this study was 443 participants. Psychological resilience is predicted by state desperation, with entrapment and intolerance of uncertainty playing a mediating role. The study findings indicate that the Turkish adaptation of the State Desperation Scale exhibits robust psychometric properties.